Pemanfaatan Teknologi Internet of Things (IoT) untuk Penguatan Materi dan Praktik Pendidikan Agama Islam (PAI) di Perguruan Tinggi - Khairuni, Nisa (Jurnal Nispatti, 2025)
This study aims to analyze the potential integration and implementation framework for the Internet of Things (IoT) in the context of Islamic Religious Education (PAI) learning in higher education. With the increasing need for PAI learning methods that are not only cognitive but also effective in practical and affective aspects (morals), IoT offers an innovative solution for creating an interactive, personalized learning environment that supports real-time worship practices. The methodology used is a comprehensive literature review, utilizing studies on the digitalization of education and PAI. The findings indicate that IoT can improve the quality of PAI through an automated attendance system, a smart lab for fiqh practice (wudu, prayer), and personalized morals materials based on students’ digital interactions. However, key challenges include religious data security, budget constraints, and the need to develop an IoT-based PAI curriculum. This study recommends collaboration between the PAI Study Program and the Faculty of Engineering to design a prototype IoT-based PAI system.